1993
DOI: 10.1002/ajmg.1320450527
|View full text |Cite
|
Sign up to set email alerts
|

New X‐linked syndrome with severe mental retardation, severely impaired vision, severe hearing defect, epileptic seizures, spasticity, restricted joint mobility, and early death

Abstract: A family with an X-linked mental retardation syndrome involving seven children in two generations is reported. The syndrome includes microcephaly, severe mental retardation, optic atrophy with severely impaired vision or blindness, a severe hearing defect, spasticity, epileptic seizures, restricted movement of the large joints, and death in infancy or early childhood. We conclude that this is a distinct, previously unrecognized X-linked mental retardation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…These include Gustavson syndrome (OMIM# 309555, X-linked mental retardation, microcephaly, optic atrophy with severely impaired vision, severe hearing defect, spasticity, epileptic seizures, restricted movement of the large joints, and death in infancy or early childhood) [Gustavson et al, 1993], Wolfram syndrome (OMIM# 222300, diabetes insipidus, diabetes mellitus, optic atrophy, and deafness) [Barrett et al, 1997], Hagemoser-Weinstein-Bresnick syndrome (OMIM# 165199, optic atrophy, early onset hearing loss, and peripheral neuropathy) [Hagemoser et al, 1989], and the X-linked Rosenberg-Chutorian syndrome (OMIM# 311070, optic atrophy, deafness, and polyneuropathy) [Rosenberg and Chutorian, 1967]. In addition, Ozden et al [2002] reported on 10 members of a three-generation family with progressive optic atrophy and progressive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…These include Gustavson syndrome (OMIM# 309555, X-linked mental retardation, microcephaly, optic atrophy with severely impaired vision, severe hearing defect, spasticity, epileptic seizures, restricted movement of the large joints, and death in infancy or early childhood) [Gustavson et al, 1993], Wolfram syndrome (OMIM# 222300, diabetes insipidus, diabetes mellitus, optic atrophy, and deafness) [Barrett et al, 1997], Hagemoser-Weinstein-Bresnick syndrome (OMIM# 165199, optic atrophy, early onset hearing loss, and peripheral neuropathy) [Hagemoser et al, 1989], and the X-linked Rosenberg-Chutorian syndrome (OMIM# 311070, optic atrophy, deafness, and polyneuropathy) [Rosenberg and Chutorian, 1967]. In addition, Ozden et al [2002] reported on 10 members of a three-generation family with progressive optic atrophy and progressive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The family studied by Huang et al [1991] has been described in detail by Pettigrew et al [1991]. The family of Malmgren et al [1993] was described in detail by Gustavson et al [1993]. Malmgren et al [ 19931 made comparisons between these disorders and speculated that there existed the possibility of a contiguous gene syndrome in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Malmgren et al [ 19931 made comparisons between these disorders and speculated that there existed the possibility of a contiguous gene syndrome in the area. If we accept that BFLS is an entity distinct from the disorders described by Gustavson et al [1993] and Pettigrew et al [19911, then a contiguous gene syndrome to account for all of the above would require the presence of a series of overlapping submicroscopic deletions or some other genetic mechanism which affects more than one contiguous locus.…”
Section: Discussionmentioning
confidence: 99%
“…Gustavson et al [] described a single family with multiple flexion contractures at birth, IUGR, congenital blindness and deafness, severe ID, seizures, microcephaly and early death. Optic atrophy, large ears, vertical talus, enlarged ventricles, underdeveloped brain with cerebellar hypoplasia, and linkage to Xq23–q27.3 was reported [Malmgren et al, ].…”
Section: Resultsmentioning
confidence: 99%